THE TRANSFORMATIVE ROLE OF TRANSLATION IN LANGUAGE EDUCATION - Gulnoza Shodibekova Ilxom qizi; Zilola Abduraxmonova (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation: The realm of language learning is a dynamic and intricate landscape where the fusion of translation and teaching methods plays a pivotal role. This article delves into the symbiotic relationship between translation and teaching methods and illuminates the manifold ways in which this intersection is transforming the approach to language education.